Sustainable snow handling - Reinosdotter, Karin (Luleå tekniska universitet, Arkitektur och vatten, 2007)
Urban snow contains pollution that originates from sources such as atmospheric precipitation, traffic emission, and de-icing chemicals. These pollutants accumulate in the snow during the winter and are released when the snow starts to melt. In Sweden, the municipal organizations are responsible for snow handling within the municipalities and the National Road Administration (SNRA) for snow handling on the main roads. Today, no general guidelines are given for how the municipalities should handle the snow, taking environmental aspects into consideration. To minimize the negative effects from snow handling, the Swedish Environmental Protection Agency presented a snow separation strategy. The purpose of this strategy was to separate urban snow into "heavily"- polluted and "less"- polluted categories. In implementing the strategy, municipalities may see difficulties arise when identifying criteria for "heavily polluted" and "less polluted" snow due to the large variations in snow quality within urban areas.The objective of this thesis was to study the conditions for developing an environmentally sustainable snow handling strategy. The research was carried out in three parts: snow handling strategies, pollutions in urban snow and pollution pathways from urban snow. First of all, a survey was conducted dealing with snow handling strategies used in a number of Swedish municipalities. The results concerning pollution in snow are based on field studies. Snow samples were collected in two Swedish municipalities and along a highway in the northern part of Sweden; the snowmelt process and the influence of road salt were studied through a laboratory experiment.The inventory of snow handling strategies in Swedish municipalities showed that the strategies have not changed much over a ten-year period. A study for the city of Luleå showed that the yearly traffic-related emissions and costs were reduced by increasing the use of local snow deposits. On the other hand, local snow deposits may lead to an increased risk of accidents ...